Advances in the Application of Natural Products and the Novel Drug Delivery Systems for Psoriasis - Xie, Jin; Huang, Shengjie; Huang, Haozhou; Deng, Xuan; Yue, Pengfei; Lin, Junzhi; Yang, Ming; Han, Li; Zhang, Ding-kun (Frontiers in Pharmacology, 2021)
Psoriasis, an incurable autoimmune skin disease, is one of the most common immune-mediated disorders. Presently, numerous clinical research studies are underway, and treatment options are available. However, these treatments focus on improving symptoms of the disease and fail to achieve a radical cure; they also have certain toxic side effects. In recent years, natural products have increasingly gained attention because of their high efficiency and low toxicity. Despite their obvious therapeutic effects, natural products’ biological activity was limited by their instability, poor solubility, and low bioavailability. Novel drug delivery systems, including liposomes, lipospheres, nanostructured lipid carriers, niosomes, nanoemulsions, nanospheres, microneedles, ethosomes, nanocrystals, and foams could potentially overcome the limitations of poor water solubility and permeability in traditional drug delivery systems. Thus, to achieve a therapeutic effect, the drug can reach the epidermis and dermis in psoriatic lesions to interact with the immune cells and cytokines.